STABILITY ANALYSIS OF DISC BRAKE SYSTEMS WITH UNCERTAINTY PARAMETERS - HUANG Ya; YU DeJie; LV Hui; PENG Long (Jixie qiangdu)
To suppress the brake noise of automotive disc brake systems,a stability analysis method of disc brake systems with random and fuzzy parameters was proposed. The proposed method was mainly based on the techniques of response surface methodology（ RSM）,complex eigenvalue analysis and reliability analysis. In the proposed method,the hybrid uncertainties existing in a disc brake system were described by random and fuzzy parameters,and the parameterized model of the damping ratio of unstable mode was established by RSM. The limit state function used to value system stable reliability was built up,and the reliability analysis was carried out for the uncertain brake system with random and fuzzy parameters. In order to explore the influence of system parameters on system stability,the parameter sensitivities were carried out by the global sensitivity analysis of Morris method. By introducing the proposed method for the stability analysis of a disc brake system with random and fuzzy parameters,the reliability and the parameter sensitivities were calculated. The numerical results show that the stability of this brake system can be improved by reducing the densities of back plates or by increasing the thicknesses of back plates.